THE MEDIATING ROLE OF JOB SATISFACTION IN THE EFFECT OF WORK-LIFE BALANCE ON EMPLOYEE ENGAGEMENT AT THE REGIONAL PUBLIC COMPANY TIRTA TOHLANGKIR - Ni Komang Fefy Intan Donarta; I Gusti Bagus Honor Satrya (Adisam Publisher, 2025)
Regional Public Company Tirta Tohlangkir is currently experiencing difficulties in fostering optimal employee engagement, which stem from factors such as excessive workloads, limited participation in organizational decision-making, and a workplace atmosphere that impedes productivity. This study seeks to examine the mediating function of job satisfaction in the relationship between work-life balance and employee engagement within the organization. Employing a purposive sampling method, the study involved 92 employees as research participants. Data were collected through structured questionnaires and in-depth interviews, then analyzed using both descriptive statistics and inferential analysis through Structural Equation Modeling–Partial Least Squares (SEM-PLS).The empirical results reveal that work-life balance significantly and positively influences employee engagement. Furthermore, a well-maintained work-life balance also enhances job satisfaction, which in turn significantly boosts employee engagement. The analysis confirms that job satisfaction plays a mediating role in the linkage between work-life balance and employee engagement. From a theoretical standpoint, this research supports the relevance of social exchange theory in the field of organizational behavior. Practically, the findings provide valuable insights for developing strategies to improve employee engagement, particularly through enhancing job satisfaction and achieving a better balance between professional and personal life.